2015
DOI: 10.1007/s11771-015-2789-y
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of fluid-induced vibrations and identification of hydrodynamic forces on flow control valves

Abstract: Dynamics and vibration of control valves under flow-induced vibration are analyzed. Hydrodynamic load characteristics and structural response under flow-induced vibration are mainly influenced by inertia, damping, elastic, geometric characteristics and hydraulic parameters. The purpose of this work is to investigate the dynamic behavior of control valves in the response to self-excited fluid flow. An analytical and numerical method is developed to simulate the dynamic and vibrational behavior of sliding dam va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…We should stress though that parallels of the mechanisms of instability we describe through interaction between fluid flow and springmass systems occur in other industrial devices and sectors. Documented cases occur for example in nuclear engineering Galbally et al (2015), steam power Yonezawa et al (2012); Bolin and Engeda (2015), automotive fuel transmission Dazhuan et al (2015) and hydraulic power transmission Mehrzad et al (2015). Similar instabilities can also be present in other valve topologies e.g.…”
Section: Introductionmentioning
confidence: 98%
“…We should stress though that parallels of the mechanisms of instability we describe through interaction between fluid flow and springmass systems occur in other industrial devices and sectors. Documented cases occur for example in nuclear engineering Galbally et al (2015), steam power Yonezawa et al (2012); Bolin and Engeda (2015), automotive fuel transmission Dazhuan et al (2015) and hydraulic power transmission Mehrzad et al (2015). Similar instabilities can also be present in other valve topologies e.g.…”
Section: Introductionmentioning
confidence: 98%
“…3,4 Undoubtedly, most researchers focused on the optimization of structural parameters. Mehrzad 5 studied the dynamic characteristics of a control valve under self-excited flow, analyzed the effects of inertia, damping, and geometric parameters on the response speed and stability of the valve, and established the corresponding numerical model. Results demonstrated that with the optimal rounded valve, vibration amplitude can be reduced by an average to 30%.…”
Section: Introductionmentioning
confidence: 99%
“…The stable boundary in the parameter space was determined via numerical simulation; the pressure control valve was then optimized by particle swarm optimization algorithm with the stable boundary as a constraint. Samad [8] analyzed the vibration characteristics of control valves of various shapes under the action of fluid exciting force to find that the vibration amplitude of a circular valve is lower than that of a flat or steep valve. Anelina [9] examined the stress and strain characteristics of a steam valve to find that changes in the time variable and non-uniform temperature field alter the local stress leading to metal fatigue.…”
Section: Introductionmentioning
confidence: 99%